2012
DOI: 10.7575/ijalel.v.1n.5p.42
|View full text |Cite
|
Sign up to set email alerts
|

The Picture of Modern Workplace Environment and Oral Communication Skills of Engineering Students of Pakistan

Abstract: Communication plays paramount role for engineers at workplace in this modern age of globalization and industrialization. The purpose of this study was to determine importance of oral communication and oral presentation for engineers at workplace and barriers that hindered effective oral presentation performance of engineering students for workplace environment. Thirty engineers and seven engineering students participated in this study. Purposive sampling method was used for data collection purpose. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The study concluded that CA significantly affects the engineers' job performance. Interestingly, engineers with high CA levels express low selfconfidence, poor body language, and nervousness in their oral presentations (Kakepoto et al, 2013). These studies have shown an inconclusive correlation between CA levels and workplace variables; hence, more investigations on CA at the workplace are needed to shed some light on the matter.…”
Section: Oral Communication Apprehension and Workplace Settingmentioning
confidence: 99%
“…The study concluded that CA significantly affects the engineers' job performance. Interestingly, engineers with high CA levels express low selfconfidence, poor body language, and nervousness in their oral presentations (Kakepoto et al, 2013). These studies have shown an inconclusive correlation between CA levels and workplace variables; hence, more investigations on CA at the workplace are needed to shed some light on the matter.…”
Section: Oral Communication Apprehension and Workplace Settingmentioning
confidence: 99%
“…A qualitative study using an observation checklist as an instrument was conducted by Kakepoto et al (2013). The study examines the CA among Pakistan's engineers with five years of experience.…”
Section: The Gaps In Communication Apprehension Studiesmentioning
confidence: 99%
“…The study concluded that CA significantly affects engineers' job performance. Interestingly, engineers with high CA levels show low self-confidence, poor body language, and nervousness in their oral presentations (Kakepoto et al, 2013). These studies have shown an inconclusive correlation between CA levels and workplace variables; hence, more investigations on CA at the workplace are needed to shed some light on the matter.…”
Section: The Gaps In Communication Apprehension Studiesmentioning
confidence: 99%
“…The ridicule and sarcasm of their peers caused them to feel nervous before the presentation began. Consequently, during presentations, students experience worries and anxiety (Lucas, 2001;Kakepoto et al, 2012).…”
Section: Statement Of Problemmentioning
confidence: 99%